Laparoscopic aspirator bracket: a new instrument facilitating the aspiration and exposure of operative field simultaneously in laparoscopic nephron-sparing surgery - Yan, Fengqi; Dou, Xiaoliang; Zhu, Guangfeng; Tang, Qisheng; Zhang, Bo; Zhao, Bo; Yu, Lei; Wang, He; Wang, Yong (Frontiers in Oncology, 2023)
Background: This study aims to describe a novel laparoscopic aspirator bracket (LAB) and its use in laparoscopic nephron-sparing surgery (NSS) by a simple enucleation (SE) technique. Methods: A total of 123 renal tumor cases who underwent laparoscopic NSS via LAB or laparoscopic aspirator between July 2017 and April 2021 were retrospectively analyzed. General characteristics, perioperative data and postoperative follow-up data of patients were compared. Results: The application of LAB in laparoscopic renal tumor SE surgery shortened the operation time (88.58 ± 38.25 vs. 102.25 ± 35.84 min, p < 0.05) and improved the zero ischemia rate (18.75% vs. 3.39%, p < 0.05), shortened warm ischemia time (16.17 ± 5.16 vs. 19.39 ± 5.62 min, p < 0.05) and decreased intraoperative blood loss (166.19 ± 111.60 vs. 209.15 ± 127.10 ml, p < 0.05). In addition, the serum creatinine and eGFR values in the LAB group also showed faster and better renal function recovery. Conclusion: The new LAB could aspirate and expose the operative field with a single instrument. In operations that need to expose and aspirate simultaneously, such as in renal tumor simple enucleation, it could shorten operation time, reduce intraoperative blood loss and improve the postoperative renal function recovery.